Exploitation of modem accounting for aims of development in libya - الحصادي, د.سالم إسماعيل (Dirasat in Economics and Business, 2004)
the purpose of this paper is to lay down the base of establishing an accounting model for the libyan environment capable of enhancing economic and social development. to this end, a methodological approach based on logical analysis of related literature, has been used, whereby three prepropositions had been examined, namely.